2005
DOI: 10.1007/s11373-004-8169-5
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 receptors in different cell types

Abstract: Galectins are a family of animal lectins defined by two properties: shared amino acid sequences in their carbohydrate-recognizing domain, and beta-galactoside affinity. A wide variety of biological phenomena are related to galectins, i.e., development, differentiation, morphogenesis, tumor metastasis, apoptosis, RNA splicing, and immunoregulatory function. In this review, we will focus on galectin-1 receptors, and some of the mechanisms by which this lectin affects different cell types. Several galectin-1 rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
111
1
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 95 publications
(109 reference statements)
2
111
1
3
Order By: Relevance
“…Gal-1 is well characterized as a lectin that can regulate cellular activity by binding specific glycoproteins on the cell surface (60,61). More recently, a role for intracellular gal-1 in regulating Ras membrane localization and downstream signaling has been reported in non-T cells (62,63).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gal-1 is well characterized as a lectin that can regulate cellular activity by binding specific glycoproteins on the cell surface (60,61). More recently, a role for intracellular gal-1 in regulating Ras membrane localization and downstream signaling has been reported in non-T cells (62,63).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CD45 and CD43 represent excellent candidate gal-1 effectors. CD3, CD4, CD7, and GM1 represent alternate known gal-1 receptors with the potential to influence TCR binding and signal transduction and synaptic dynamics (13,15,19,29,60). A direct assessment of gal-1 effects on glycoprotein counterreceptor organization on CD8 T cells is necessary, because it is becoming increasingly clear that galectins can have alternate activities on distinct T cell subpopulations (8,9,69).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the carbohydrate-binding ability, galectin-1 associates with proteins through protein-protein interactions and participates in a variety of oncogenic processes including transformation and proliferation, cell cycle regulation, cell adhesion, metastasis, inhibition and the promotion of programmed cell death and apoptosis in activated T cells (10,11). Numerous ligands for galectin-1 have been described in different tissues and cells that include actin, laminin, fibronectin, vitronectin, integrins, CA-125, H-ras, CD45 and gemin-4 (6,(12)(13)(14)(15). Galectin-1 is expressed in a variety of cell types including breast epithelial, thymic epithelial, endothelial and dendritic cells, macrophages, fibroblasts and bone marrow cells (2,(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Only small numbers of microvessels were observed in tumors of Gal-1-null mice, indicating that Gal-1 is crucial for tumor angiogenesis (Thijssen et al, 2006). Gal-1 can bind to cell-surface receptors such as integrins (Fischer et al, 2005) and several cluster of differentiation (CD) receptors (Elola et al, 2005), and to extracellular matrix components fibronectin and laminin (Gu et al, 1994), to exert its functions extracellularly. More recently, studies have shown that various glycosylation patterns of cell surface glycoproteins on different types of T-helper and cancer cells modulate the susceptibility of these cells to Gal-1-induced apoptosis (Toscano et al, 2007;Valenzuela et al, 2007).…”
mentioning
confidence: 99%